Nerve decompression surgery suppresses TNF‐ɑ expression and T cell infiltration in a rat sciatic nerve chronic constriction injury model. Issue 11 (4th February 2022) - Mukai, Michiaki; Uchida, Kentaro; Inoue, Gen; Satoh, Masashi; Miyagi, Masayuki; Yokozeki, Yuji; Hirosawa, Naoya; Matsuura, Yusuke; Ohtori, Seiji; Takaso, Masashi
Abstract: Decompression surgery (DS) is a standard treatment for chronic nerve compression injuries; however, the mechanisms underlying its effects remain unclear. Here, we investigated the effects of DS on messenger RNA (mRNA) expression of tumor necrosis factor‐α (TNF‐α) and T cell recruitment in a rat sciatic nerve (SN) chronic constriction injury (CCI) model. Male Wistar rats were subjected to CCI to establish a model of SN injury (CCI group). DS, in which all ligatures were removed, was performed 3 days after CCI surgery (CCI + dec group). Mechanical sensitivity was assessed using the von Frey test 3, 7, and 14 days after the CCI surgery. Gene expression of Tnfa, Cd3, Cxcl10, and immunolocalization of TNF‐α and the pan T cell marker, CD3, was evaluated using quantitative polymerase chain reaction (qPCR) and immunohistochemistry, respectively. In addition, the effects of TNF‐α on Cxcl10 expression and CXCL10 protein production were evaluated using qPCR and enzyme‐linked immunosorbent assay in SN cell culture. Rats that received DS had significantly higher withdrawal threshold levels than those in the CCI group. In addition, Tnfa, Cd3, and Cxcl10 mRNA expression increased following CCI. DS suppressed this elevated expression, with the CCI + dec group showing significantly reduced expression levels compared to the CCI group. Furthermore, TNF‐α induced Cxcl10 expression and CXCL10 protein production in SN cell culture. Therefore, DS reduced TNF‐α expression and T cell recruitment in the rat SN CCI model. These observations may partly explain the mechanism underlying the therapeutic effects of DS. Abstract : We investigated the effect of decompression surgery (DS) on messenger RNA (mRNA) levels of tumor necrosis factor‐α (TNF‐α) and T cell recruitment in a rat sciatic nerve (SN) chronic constriction injury (CCI) model. DS significantly increased withdrawal threshold levels and suppressed elevated Tnfa, Cd3, and Cxcl10 mRNA expression in CCI rats. Furthermore, TNF‐α induced the production of CXCL protein in SN cells. Our findings suggest that DS‐induced pain relief may arise as a result of the suppression of TNF‐α and T‐cell infiltration.